2020
DOI: 10.3390/su12177019
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Enzymatically Induced Calcium Carbonate Precipitation in the Retention of Heavy Metal Ions

Abstract: This study evaluated the efficacy of enzyme induced calcite precipitation (EICP) in restricting the mobility of heavy metals in soils. EICP is an environmentally friendly method that has wide ranging applications in the sustainable development of civil infrastructure. The study examined the desorption of three heavy metals from treated and untreated soils using ethylene diamine tetra-acetic acid (EDTA) and citric acid (C6H8O7) extractants under harsh conditions. Two natural soils spiked with cadmium (Cd), nick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 90 publications
0
27
0
Order By: Relevance
“…Considering that PVA fiber has fine resistance to acid, alkali, salt, wear, sunlight, and corrosion, the test used high-strength and high elastic modulus PVA fiber [ 15 , 16 ]. The test also adopted standard silica sand from Xiamen, China, whose particle distribution is shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Considering that PVA fiber has fine resistance to acid, alkali, salt, wear, sunlight, and corrosion, the test used high-strength and high elastic modulus PVA fiber [ 15 , 16 ]. The test also adopted standard silica sand from Xiamen, China, whose particle distribution is shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Low-carbon solutions for the stabilization of contaminated soils [21,22] and bioengineering techniques to prevent soil erosion [23] are put forward as relevant contributions to the planet's sustainability.…”
Section: Overview Of the Special Issuementioning
confidence: 99%
“…Moghal et al [22] evaluate the efficacy of enzymatically induced calcite precipitation in the retention of heavy metal in soils. Soils contaminated with cadmium (Cd), nickel (Ni), and lead (Pb) were treated with three types of enzyme solutions.…”
Section: Highlights Of the Contributionsmentioning
confidence: 99%
“…The results from their study indicated that the concentrations of As, Mn, Zn, Pb, Cr and Cu were reduced by 31.7%, 65.8%, 50.6%, 51.6%, 45.1% and 49.7%, respectively. Moghal, Lateef [99] and Moghal, Lateef [131] investigated the efficacy of the EICP method on adsorption and desorption of soils mixed with different combinations of heavy metals. Their results indicated that EICP could immobilize to a significant level the heavy metals in selected soils.…”
Section: Removal Of Heavy Metalsmentioning
confidence: 99%